(untitled) (GAIMS Journal of Medical Sciences, 2026)
Background: Anaemia disproportionately affects tribal populations in India due to nutritional deficiencies, haemoglobinopathies, and limited healthcare access. Community-level data from tribal districts of Gujarat are lacking. Aims and Objectives: To assess the prevalence, severity, and morphological patterns of anaemia among tribal children and adolescents in Chhotaudepur district, Gujarat, and to evaluate its association with socio-demographic and anthropometric variables. Study Design: Community-based cross-sectional study. Setting: Government residential school, Kawant taluka, Chhotaudepur district, Gujarat, India (February–March 2025). Materials and Methods: A total of 1,478 tribal participants aged 10–20 years were enrolled. CBC was performed on a Sysmex XP-300 analyser; anaemia was classified by WHO 2011 haemoglobin thresholds (age- and sex-stratified) and morphologically by MCV/MCH. Sickling solubility test (2% sodium metabisulphite) was used for haemoglobinopathy screening. Statistics: IBM SPSS v25.0; chi-square, Fisher’s exact, independent t-test, and Spearman correlation; p<0.05 considered significant. Results: Anaemia prevalence was 60.08% (95% CI: 57.6–62.6%). Among anaemic participants, 63.96% had mild, 33.33% moderate, and 2.70% severe anaemia. Microcytic anaemia was the predominant morphological type (95.27%); no macrocytic anaemia was detected. Sickling solubility test positivity was observed in 10.22% of participants. Anaemia was significantly associated with caste (p=0.005) but not with age, sex, below poverty line status, or anthropometric parameters. Conclusion: Anaemia is highly prevalent among tribal school-going children in Chhotaudepur, with a predominantly microcytic pattern likely due to iron deficiency, as confirmatory iron studies were not performed. Scheduled Tribe membership was the sole significant socio-demographic predictor. Targeted nutritional interventions, iron supplementation, and haemoglobinopathy electrophoresis-based screening are warranted.